The integral representation of the solution of mixed parabolic problem in piece-homogeneous polar axis with soft limits - Konet, I.M.; Pylypiuk, T.M. (Математичне та комп'ютерне моделювання. Серія: Фізико-математичні науки, 2013)
By means of method of hybrid integral transform of Legendre-Bessel-Legendre type with the spectral parameter the integral representation of exact analytical solution of mixed problem for the system of equations of parabolic type in the piece-homogeneous polar axis r ≥ R0 ≥ 0 with soft limits is obtained. Modeling of evolutionary process is made by the method of hybrid differential Legendre-Bessel-Legendre operator. Методом гібридного інтегрального перетворення типу Лежандра-Бесселя-Лежандра зі спектральним параметром одержано інтегральне зображення точного аналітичного розв'язку мішаної задачі для системи рівнянь параболічного типу на кусково-однорідній полярній осі r ≥ R0 ≥ 0 з м'якими межами. Моделювання еволюційного процесу здійснено методом гібридного диференціального оператора Лежандра-Бесселя-Лежандра.